Coconut-Based Product Innovations: Gluten-Free Coconut Flour and Face Masks from Coconut - Okta, Fauzia Noprima; Yesika, Relin; Haque, Aina Fatkhil; Oktarini, Rizki; Zahra, Farah Az; Khaliq, Iyas Nur; Vebson, Anugrah Adha; Utami, Kharunia Tri; Putri, Firda Vemilia; Amani, Muhammad Muzhaffar (Indonesian Journal of Community Empowerment (IJCE), 2025)
Coconut (Cocos nucifera L.) is a cultivated tree due to its many benefits. Coconut can be processed into coconut water, coconut milk, coconut sugar, and coconut oil. The waste from VCO processing can be used as coconut flour. Coconut flour can be processed into gluten-free foods that are beneficial for health. Coconut flour is produced by drying coconut pulp, roasting, grinding, and sieving. The resulting coconut flour has a pure white to yellowish white color with a distinctive coconut aroma. Coconut flour is processed into healthy, non-gluten foods for diabetics, such as gluten-free banana cake. Coconut water can be used as a facial mask that functions to moisturize the skin. Community service activities by utilizing the potential of natural resources in Panca Mukti village are very targeted. Based on the results of the questionnaire, there was an increase in community knowledge after the extension and training activities were carried out. This activity also aims to improve the community's economy by utilizing coconut pulp.